Minimal Clinically Important Difference for 6-Minute Walk Distance in Singaporean Adults with Chronic Respiratory Diseases - Meredith T LYEUNG; Alan W P WONG; Katherine S L HUANG; Alice Y M JONES (康复学报, 2015)
Objective:The 6-minute walk distance(6MWD)is a common measure of functional exercise capacity in clinical populations, particularly in patients with chronic respiratory diseases. While some literature has documented the minimal clinically important difference(MCID)of the 6MWD in the Caucasian population, information on the Asian population is scanty. This study aimed to establish the MCID of the 6MWD in Asian adults with chronic respiratory diseases(CRDs).Methods:Data from the“Pulmonary Rehabilitation Programme Registry, Singapore General Hospital”were analysed. Both the“anchor-based”and“distribution-based”methods were used to estimate the MCID of the 6MWD. Fifty participants(38 males and 12 females)with a mean age of 64.2 years(SD 12.3)diagnosed with CRDs involved in the“anchor-based”method for determination of MCID of 6MWD. These participants were interviewed by telephone and rated their perceived change of improvement after pulmonary rehabilitation program using the Global Rating of Change(GROC)scale;the change in 6MWD before and after the program in these patients were compared with their perceived improvement and such relation is illustrated by the receiver operating characteristic curve(ROC). To determine the MCID of 6MWD by the“distribution-based”method, medical records of participants from the outpatient and inpatient pulmonary rehabilitation program(PRP)were retrieved from 136 patients(103 males and 33 females), mean age of 60.1 years(SD 14.1).Results:This study showed that the ROC curve indicated an optimal cut-off value for clinically significant change in the 6MWD was 17.4 metres. This corresponded to a sensitivity of 79.4%, and specificity of 81.3%, positive likelihood ratio is 4.23. The MCID of 6MWD determined by the distribution-based estimation was 18.6 metres.Conclusion:The more conservative value of 18.6 metres is considered to be the appropriate MCID estimate for 6MWD for Chinese people with CRDs in Singapore.